Lipid profile in different grades of Ultrasonic Non-Alcoholic Fatty Liver Disease - Bhusal, Khem Raj; Simkhada, Rabindra; Nepal, Pramod (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: This study was conducted with objective of studying the lipid abnormalities in patients with non-alcoholic fatty liver disease diagnosed on the basis of ultrasound. Materials & Methods: Total 100 patients consisting of 67 males and 37 females diagnosed as Non-alcoholic fatty liver disease on the basis of ultrasound were included in the study. Laboratory values of different lipid parameters were compared in different grades of these patients. Results: Out of total 100 cases, mild nonalcoholic fatty liver disease was found in 83 %, moderate in 17 % and severe in none of the participants. Age of the participants ranged from 26 to 79 years with mean being 45 ± 11.99 years. Presence of dyslipidemia was found in 94 % of the cases. Triglycerides, total cholesterol and low density lipoprotein levels were raised in 59, 53, 72% of the cases respectively and High density lipoprotein level was decreased in 57% of participants. There was significant positive correlation of presence of non-alcoholic fatty liver disease with increasing levels of serum total cholesterol (P value <0.001), low density lipoprotein (P value <0.001) and triglyceride (P value <0.001) and significantly decreasing high density lipoprotein (P value <0.001). Whereas increasing grades of non-alcoholic fatty liver disease weren’t significantly associated with increasing level of lipid abnormalities. Conclusion: This study showed the high prevalence of dyslipidemia in non-alcoholic fatty liver patients. Early detection with simple non-invasive ultrasonography is very useful to detect dyslipidemic patients.